Cost and Time Analysis of Project Acceleration using the Crashing Method with Additional Working Hours and Labor - Lutfi, Moh Ali; Witjaksana, Budi; Purnama, Jaka (Pelopor Publikasi Akademika, 2025)
This study aims to analyze project cost and time acceleration using the Crashing Method by adding three hours of overtime work and additional labor. Delays in construction projects often lead to budget overruns and inefficiencies, making acceleration techniques essential for ensuring timely project completion. The research evaluates cost efficiency by comparing the total project budget before and after implementing the Crashing Method. Using both qualitative and quantitative approaches, this study examines the impact of different acceleration strategies on cost increase and time reduction. The findings indicate that project completion time can be significantly reduced using both methods; however, overtime results in higher cost increases compared to additional labor. While overtime provides immediate acceleration, it incurs higher expenses due to increased labor wages, whereas adding workforce results in gradual but more cost-effective acceleration. Furthermore, the study underscores the importance of selecting the appropriate acceleration approach based on project constraints, workforce availability, and financial considerations. Effective resource allocation, labor management, and risk assessment are critical factors in minimizing costs while maximizing efficiency. By analyzing the trade-offs between cost and time, this study provides valuable insights into the optimal strategy for project acceleration in construction management. The findings offer practical recommendations for contractors, project managers, and stakeholders to optimize resources and maintain budget control while ensuring project completion within the scheduled timeframe.